Characteristics and Trajectory of Older Adults Supported by a Patient Navigator Program in a Hospital Setting: A Cohort Observational Study - Liu, Grace; Kokorelias, Kristina M.; Knoepfli, Amanda; Dasgupta, Tracey; Ziegler, Naomi; Guilcher, Sara J.T.; Hitzig, Sander L. (Canadian journal on aging, 2025)
To improve transitions in care, a new patient navigation (PN) program was introduced to support older adults with complex care needs transition from hospital to home. The patient navigator is a community social worker embedded in the hospital’s care teams. A cohort observational design was used to conduct the study by analysing the patient navigator’s clinical notes and hospital’s administrative data to describe the characteristics of patients, scope of the patient navigator’s activities, and patient outcomes. Ninety patients were assigned to the patient navigator’s caseload (November 2019–November 2021) in which the average age was 78.9 (range 55–95). The most frequent PN intervention types were referrals to community services (66%, n = 59) and discharge planning (61%, n = 55). The patient navigator supported 66% patients (n = 59) in returning home and provided follow-up care for 74 days (average). This study provides important insights into the patient navigator’s role to guide decision makers in implementing PN programs for older adults in a hospital setting.